Evaluation of a nationally disseminated self-help intervention for smoking cessation ('Quit Kit'). Issue 5 (17th March 2011) - Ussher, Michael; Chambers, Melanie; Adams, Ryan; Croghan, Emma; Murray, Rachael
Abstract : Objective: To assess the extent of uptake and impact of a nationally disseminated self-help intervention for smoking cessation ('Quit Kit'). Methods: The kit contained practical tools for supporting quit attempts. Of 480 000 individuals receiving the kit, telephone interviews were conducted with 2347 randomly selected individuals. Interviews assessed the impact of the kit on smoking behaviours and on attitudes to the intervention and to health service support. Results: The majority of interviewees reported the kit as being helpful for stopping smoking (61%) and agreed that, having received the kit, they would be more likely to consider the National Health Service for help with quitting (84%). Younger interviewees were significantly more likely to report the kit as helpful, to say they would recommend it to others and to agree that it increased their confidence in quitting (all p≤0.001). As a result of receiving the kit, 29%, 17% and 11% of interviewees, respectively, reported visiting their doctor, pharmacist or stop-smoking service for help with quitting. The kit was reported to have triggered a quit attempt among around half (57%) of those receiving it. When only including those who had received the kit at least 1 month prior to interview, 26.5% (126/475) of those attempting to quit reported remaining completely abstinent from smoking for at least a month. Conclusions: The findings suggest that distributing a self-help intervention for smoking cessation at a national level may be successful in terms of uptake of the intervention, triggering quit attempts and aiding smoking cessation.